1952
DOI: 10.1099/00221287-6-3-4-261
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of a Direct- and a Plate-counting Technique for the Quantitative Estimation of Soil Micro-organisms

Abstract: SUMMARY:Estimates of numbers of micro-organisms occurring in three differently manured soils, made by a direct-counting and plating technique, were compared. No correlation was found between the two methods and reasons for the large discrepancy between them are discussed. Contradictory information of the effect of external factors on soil micro-organisms can be given by the two different methods of counting.Estimates of the total numbers of bacteria in soil obtained by a direct-counting technique devised by Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
4

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 9 publications
2
62
0
4
Order By: Relevance
“…The limitations of determining bacterial or fungal cfu that are representative of microbial communities by plate counts have been examined by numerous researchers (Butterfield 1932, Egdell et al 1960, Gossling 1958, Jensen 1962, Skinner et al 1952, Weiringa 1958; the general consensus is that plate counts are by no means quantitative for the total microbial community and only represent a fraction of the total. Moreover, this fraction also does not represent an absolute value but a relative value dependent on well controlled and reproducible laboratory techniques, as well as the composition of the plating media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of determining bacterial or fungal cfu that are representative of microbial communities by plate counts have been examined by numerous researchers (Butterfield 1932, Egdell et al 1960, Gossling 1958, Jensen 1962, Skinner et al 1952, Weiringa 1958; the general consensus is that plate counts are by no means quantitative for the total microbial community and only represent a fraction of the total. Moreover, this fraction also does not represent an absolute value but a relative value dependent on well controlled and reproducible laboratory techniques, as well as the composition of the plating media.…”
Section: Discussionmentioning
confidence: 99%
“…The use of plate count techniques in estimating bacteria communities in soil have been critically evaluated by numerous researchers (Butterfield 1932, Skinner 1952, Weiringa 1958, Gossling 1958, Egdell et al 1960, Jensen 1962. A primary criticism concerns the inability to measure the total bacterial community in soil using a given growth medium because a given growth medium is selective for certain bacteria present.…”
Section: Field Studiesmentioning
confidence: 99%
“…Not only were the plate counts of classical microbial ecology underestimated by one to five orders of magnitude, but there were spiral-shaped organisms seen in direct counts of formaldehyde-treated dilutions that were not seen in plate counts. Other studies have shown no correlation between direct and plate counts (Skinner et al, 1952). Indeed whole groups of unusual shaped organisms have been seen to grow in special flattened capillary tubes implanted in soils and aqueous sediments.…”
Section: ) Plate Counts Versus Direct Microscopic Countsmentioning
confidence: 99%
“…Microbial biomass-C (MBC) and -N (MBN) were estimated by using chloroform fumigation incubation method as described in Horwath and Paul (1994). Soil microbiological properties and microbial counts were estimated by using standard methods described by Jones and Mollison (1948) and Skinner et al, (1952).…”
Section: Methodsmentioning
confidence: 99%